MULTINATIONAL COMPANIES FOR BUSINESS INTERNATIONALIZATION THROUGH FOREIGN DIRECT INVESTMENT (FDI) IN GLOBALIZATION: TRENDS FOR VALUES - Anis BENABED (Eastern European Journal of Regional Studies, 2024)
This paper analyzes and describes multinational companies as a business internationalization strategy through foreign direct investments FDIs for business internationalization to reach business values in the frames of globalization. The analysis and results demonstrated that Multinational companies (MNCs) and foreign direct investments (FDIs) may face challenges and risks in new locations, economic and political instability, difficulties of infrastructure, distrust in the locations, locations, difficulties of balance in payment, challenging negotiations in business agreements and quality contracts, borders and transportation challenges, challenging in the market size. Multinational companies that go for foreign direct investment have an economic impact and can affect a country's economy in various ways, for example, in the balance of payments, in growth rates and in job creation. The effect of foreign direct investment by multinational companies can be negative or positive depending on certain factors. A multinational company’s pattern of internationalization represents different factors of possibilities, costs, risks and difficulties faced during its internationalization. In conclusion, Foreign direct investment (FDI) is an important step towards business internationalization and if the domestic company decides to go multinational towards FDI, it has to consider the factors of ownership, location and internalization to reach business internationalization as confirmed in Dunning’s framework and this analysis.